Cognitive Processes In The Formation Of Language Meaning - Komala, Imas; Ari Wardani, Yulinda; Gede Mulawarman, Widyatmike; Suhatmady, Bibit (Sahabat Publikasi, 2025)
The meaning of language is influenced not only by linguistic structures, but also by the cognitive processes that occur in the human mind. This article discusses how cognitive processing, such as perception, memory, and reasoning, plays a role in the formation of language meaning. This study uses a theoretical approach that integrates cognitive linguistics with psychological science to explain the relationship between mental representation and meaning. The results of the study show that the formation of meaning is a dynamic process involving sensory experience, social context, and pragmatic use of language. This knowledge is expected to enrich insights into how humans understand and use language in various communication situations. The cognitive process in the formation of language meaning includes several main stages, namely sensing, storage in working memory, and interpretation based on context. This process depends on the mental schema that the individual has, which is acquired through social experiences and interactions. Cognitive processing is also influenced by factors such as cultural bias, individual experience, and level of familiarity with a language. Meaning is not static, but rather evolves over time and depends on the dynamics of communication. In linguistic interactions, individuals utilize mechanisms such as analogies and associations to understand new or complex meanings. Cognitive processes play an important role in the formation of language meaning. Meaning is determined not only by grammatical structure but also by the way individuals process information through experience and context. This research emphasizes the importance of a multidisciplinary approach to understanding the dynamics of meaning formation, which involves linguistics, psychology, and sociology. By understanding this process, we can improve strategies for language teaching, translation, and intercultural communication.